Agonistic beta 2-Adrenergic Receptor Autoantibodies Characterize the Aqueous Humor of Patients With Primary and Secondary Open-Angle Glaucoma - Hohberger, Bettina; Worn, Max; Lämmer, Robert; Mahajan, Aparna; Mardin, Christian; Schlötzer-Schrehardt, Ursula; Kunze, Rudolph; Herrmann, Martin; Wallukat, Gerd (Frontiers in Immunology, 2021)
Purpose
CRIS-Team WoS Importer:2021-05-28